Service Quality of Room Service During Pandemi Covid-19 - I Gusti Agung Made Mas Yuliantari; Ni Luh Eka Armoni; Ida Ayu Elistyawati (Jurnal Sains Terapan Pariwisata, 2021)
This study examines the analysis of room service quality in increasing guest satisfaction during the covid-19 pandemic at Kayumanis Jimbaran Private Estate & Spa. This study aims to determine whether the dimensions of service quality namely tangible, reliability, responsiveness, assurance, and empathy affect guest satisfaction at Kayumanis Jimbaran Private Estate & Spa. This study uses a five-dimensional analysis of service quality in the servqual (service quality) model. The population of this study is guests who stay and have experienced the quality of room service as many as 55 respondents with the method of determining the sample, namely accidental sampling. The data collected was analyzed using a questionnaire and then analyzed using the Servqual Test which describes the gap (gap) in the quality of service expected (expectations) and reality (perceptions) received by guests staying at Kayumanis Jimbaran Private Estate & Spa. Furthermore, it is analyzed using Importance Performance Analysis (IPA) which is presented in a Cartesian diagram. The results of the Servqual analysis show that there are more positive gaps than gaps with negative values. Based on the results of the Importance Performance Analysis (IPA) in the Cartesian diagram, it shows that the quality of room service services has 2 indicators in quadrant A, which means that indicators in this quadrant need to be prioritized because they are considered important by guests, namely the indicator of the accuracy of room service in serving food and drinks on the attribute (Q5), on the indicator in serving food and drinks to the estate a maximum of only 2 room service staff on the attribute (Q8 ). In addition, the results of the study show that the dominant room service quality is in quadrant B, which means that the room service at Kayumanis Jimbaran Private Estate & Spa is in a satisfactory category and is necessary to maintain its performance.